Effect of the cBN Content and Sintering Temperature on the Transverse Rupture Strength and Hardness of cBN/Diamond Cutting Tools - Kir, Durmus; Islak, Serkan; Celik, Halis; Celik, Ertugrul (Int Inst Science Sintering (I I S S), 2012)
The aim of this work was to investigate the effect of cBN content and sintering temperature on the transverse rupture strength (TRS) of cBN/diamond cutting tools produced by hot pressing. The segments containing different cBN content were manufactured under 35 MPa pressure at 600, 650 and 700 degrees C with a 3 minutes sintering time. The TRS of segments were determined using three-point bending test. Microstructure and phase composition of fracture surface of segments were determined by scanning electron microscopy (SEM), and X-ray diffraction (XRD) analysis. The obtained results show that the TRS of the segments with cBN were higher than that of the segments with diamond.
Keywords: cBN/diamond cutting tools; Hot-pressing; TRS